2019
DOI: 10.1002/tesj.482
|View full text |Cite
|
Sign up to set email alerts
|

Exploring TESOL teacher educators as learners and reflective scholars: A shared narrative inquiry

Abstract: Recent scholarship examining how teachers and teacher educators learn to teach has advocated for a more critically oriented and better developed pedagogy of teacher education, in which teacher educator as practitioner is both in evidence and examined. Yet we currently know little about teacher

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 50 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…For instance, Rosa (2019) explicitly explored the profound consequences of teachers’—and school administrators’—raciolinguicized identities for their relationships with students, their teaching, and the school and classroom communities that they imagine and create. In our own collaborations with teacher education colleagues, we also work to explicitly engage the consequences of our raciolinguicized subjectivities—the interplay between race and standardized language ideologies, for instance (Daniels, 2018; Peercy, Sharkey, Baecher, Motha, & Varghese, in press; Snyder, Park, Varghese, & Daniels, 2019).…”
Section: Poststructuralism and Teacher Subjectivitymentioning
confidence: 99%
“…For instance, Rosa (2019) explicitly explored the profound consequences of teachers’—and school administrators’—raciolinguicized identities for their relationships with students, their teaching, and the school and classroom communities that they imagine and create. In our own collaborations with teacher education colleagues, we also work to explicitly engage the consequences of our raciolinguicized subjectivities—the interplay between race and standardized language ideologies, for instance (Daniels, 2018; Peercy, Sharkey, Baecher, Motha, & Varghese, in press; Snyder, Park, Varghese, & Daniels, 2019).…”
Section: Poststructuralism and Teacher Subjectivitymentioning
confidence: 99%
“…In the second cycle of analysis, the identified codes with their associated chunks of data were grouped into themes with reference to existing literature on language teacher educators (e.g., Golombek, 2015; Peercy et al., 2019; Yuan, 2017) as well as the perspective of CT to answer the first research question. For instance, informed by the notion of emotional intelligence with both intrapersonal and interpersonal dimensions (Goleman, 1995; Salovey & Mayer, 1990), codes such as “relating to teachers” and “accepting the reality and his own limitations” were categorized under the theme of “emotional intelligence for maintaining personal emotional wellbeing and channeling emotions for effective teaching”, which constituted a key component of the participants’ expertise.…”
Section: Discussionmentioning
confidence: 99%
“…Owning to language teacher educators’ crucial role in second language teacher education, increasing research attention has been paid to this professional group, looking into their professional knowledge, practice and development. For instance, some research (Peercy, Sharkey, Baecher, Motha, & Varghese, 2019; Yuan, 2017) has shown that language teacher educators need to foster a comprehensive knowledge base to guide their everyday practice. For one thing, they need to acquire knowledge of the English language, including its literature and culture as well as its complex roles and status in specific social and professional settings.…”
Section: Who Are Efl Teacher Educators?mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the participants made sense of their situated practices, beliefs and disciplinary knowledge through a reflexive disposition (Farrell and Kennedy, 2019). The participants demonstrated not only awareness of disciplinary knowledge but also dimensions such as reflection to understand the complexity of their situated practice and language teacher education pedagogy (Johnson and Golombek, 2020;Peercy et al, 2019;Yuan and Hu, 2018). Hence, the ELT teacher educators in this study were oriented towards community-based funds of knowledge (except for Aurelia's reference to her experience as a mother); their funds could be associated with the types of knowledge that usually constitute the knowledge base in ELTE (Johnson, 2009;Le, 2020).…”
Section: Discussionmentioning
confidence: 99%